The Effect Of Postmodern Leadership, Work-Life Balance, And Perceived Organizational Support On Job Satisfaction And Its Implications For Lecturer Performance : Survey At Private Universities In East Priangan - Adi Robith Setiana; Sidik Priadana; Ina Ratnamiasih (Jurnal Publikasi Ilmu Manajemen, 2026)
This study examines the effects of postmodern leadership, work-life balance, and perceived organizational support on job satisfaction and its implications for lecturer performance at private higher education institutions in East Priangan, Indonesia. A quantitative, descriptive-verificative, cross-sectional survey design was employed. The study involved 283 lecturers selected through cluster proportional random sampling. Data were analyzed using Structural Equation Modeling (SEM) with LISREL 8.80 to assess the structural relationships among the constructs and the overall goodness of fit. The results show that postmodern leadership (β = 0.2853; t = 2.7687), work-life balance (β = 0.3191; t = 3.5139), and perceived organizational support (β = 0.3374; t = 4.5170) each have a positive and significant effect on job satisfaction. Simultaneously, the three antecedents explain 73.16% of the variance in job satisfaction. Job satisfaction, in turn, has a strong positive effect on lecturer performance (β = 0.9153; t = 15.6586; R² = 0.8378). The model also demonstrates acceptable fit, including GFI = 0.9028, RMSEA = 0.0713, TLI = 0.9518, and CFI = 0.9603. These findings indicate that lecturer performance is strengthened not only by managerial arrangements but also by leadership practices that are adaptive and participatory, realistic work-life balance policies, and consistent institutional support. The study contributes an integrated human resource management model for private higher education by positioning job satisfaction as the principal mechanism linking organizational conditions with lecturer performance.